Congress (Ship) logbook - Congress (Ship)
Logbook (172 pages) of a whaling voyage to the Indian Ocean in the ship Congress, of New Bedford, Mass. The ship's master was John C. Hamblin, and the logbook (1857 Jan.-1858 May) was kept by Caleb O. Hamblin. The volume also includes entries (1859-1863) relating to whaling voyages of the ship Governor Troup, kept by R. Kelley, and disbursements (1863-1866) relating to the ship Robert Edwards, also kept by Caleb O. Hamblin. Also includes newspaper clippings concerning Abraham Lincoln.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hamblin, Caleb O; Hamblin, John C; Kelley, R; Lincoln, Abraham, -- 1809-1865.; Governor Troup (Ship); Robert Edwards (Ship); Ship's papers -- 19th century; Voyages and travels; Whaling -- Indian Ocean; Whaling -- Massachusetts -- New Bedford; Indian Ocean -- Description and travel